The Role of Islamic Religious Education in the Formation of Student Morals at SMA Muhammadiyah 1 Klaten - Muhammad Malik Fikry Al Farros; Hafidz (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to investigate the role of Islamic religious education in shaping the morals of students at SMA Muhammadiyah 1 Klaten. Islamic religious education has an important role in shaping the character and morals of students, especially in religion-based schools such as SMA Muhammadiyah 1 Klaten. The research method used is a case study by collecting data through interviews, observation and document analysis. The results of the research show that Islamic religious education at SMA Muhammadiyah 1 Klaten plays a significant role in the formation of student morals. In Islamic religious education, students are taught moral values, ethics and Islamic principles which include honesty, justice, compassion and example. Students are also taught to apply these values in their daily lives. The learning approach used by Islamic religious educators at SMA Muhammadiyah 1 Klaten involves discussions, case studies, and student participation in useful social activities. This helps students to understand and internalize Islamic values more deeply.